Working with adolescent violence and abuse towards parents: approaches and contexts for intervention - Holt, Amanda (Routledge, 2016)
Building respectful family relationships : partnering restorative practice with cognitive behavioral skill learning / Gregory Routt and Lily Anderson -- Empowering parents : the "Who's in charge?" program / Eddie Gallagher -- Helping abused parents by non-violent resistance / Haim Omer -- Trauma-based approaches to working with parent abuse / Jane Evans -- Responding to filio-parental violence : family dynamics and therapeutic intervention / Roberto Pereira -- Parent abuse in South Island, New Zealand : delivering interventions in child and adolescent mental health services / Latesha Murphy-Edwards -- The Yuva young people's service : a holistic approach to addressing child-to-parent violence in London / Ester McGeeney, Fiona Barakat, Gjori Langeland, and Shem Williams -- The youth offender diversion alternative (YODA) community-based project for youth-to-family violence in Texas / Kristin Bolton, Peter Lehmann & Catheleen Jordan -- Gender and adolescent-to-parent violence : a systematic analysis of typical and atypical cases / Kathleen Daly and Danielle Wade -- Special considerations when working with adolescent violence and abuse in the home / Jo Howard and Amanda Holt -- Working with adolescent violence and abuse towards parents : reflections and concluding thoughts / Amanda Holt